Plant Load Factor-Key Parameter for Evaluation of Performance of Thermal Power Plant - Dr. R. K. Cham, Vilas S. Motghare, (International Journal of Scientific Research and Management (IJSRM), 2015)
The installed capacity of electricity sector till November 2014 was 255.012 GW and actual generation was found to be around 703 BU for the period April - November 2014. The performance of a power plant can be expressed through some common performance factors; one of them is Plant Load Factor (PLF). It is the key parameter for evaluation of performance of any thermal Power plant. Improving performance of power plants through interventions aimed at strengthening O & M practices, coupled with required rehabilitation and life extension interventions is perhaps the quickest and least cost alternative for augmenting availability of power in the Indian context. In this paper, relation between the availability of the plant and PLF has been discussed. Keywords: Availability factor, Plant load factor, Power Generation, Coal fired thermal Power Plants.